Moments of collusion? Close readings of affective, hidden moments within feminist research. (March 2017) - Falconer, Emily
Abstract: This paper addresses affective 'moments of collusion' present in feminist research relationships, and contextualises these seemingly personal encounters within a wider systematic framework of the early career researcher and the increasingly neoliberal climate of academia. Focusing on the temporal transition from doctoral research to postdoctorate research positions immediately post-PhD, this paper questions the concept of collusion within (immersive) fieldwork, and examines the delicate and complex question of who is colluding with whom, and for what purpose at different times within the early career academic journey. Specifically, this paper focuses on how the increasing pressures of the neoliberal university play out on our emotions and bodies during fieldwork, an area which still requires attention within the growing critiques of the affects of neo-liberalism in Higher Education. Using personal case studies as springboard for a far wider and important discussion, this paper situates such methodological dilemmas within a broader temporal framework of the increasingly precarious nature of early career academics, where 'moments of collusion' may be the only way to keep your head above water.